2021
DOI: 10.1186/s12882-021-02502-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis associated with antineutrophil cytoplasmic antibody following cimetidine treatment: a case report

Abstract: Background Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis usually induces rapidly progressive glomerulonephritis, including pauci-immune necrotizing crescentic glomerulonephritis. Acute tubulointerstitial nephritis (ATIN), which is often drug-induced, is a frequent cause of kidney injury. However, ATIN associated with ANCA without any glomerular lesions has been rarely reported, and drug-induced ATIN associated with ANCA is not well recognized. Here we present a case of an old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…In this context, experimental studies have already shown that platelets are main contributors to microvascular injury and rarefaction of tubulointerstitial capillaries (49). In ANCA-associated renal vasculitis, the occurrence of tubulointerstitial injury independent of glomerular lesions has already been described (50)(51)(52)(53). Our observations might indicate that the tubulointerstitial compartment is particularly susceptible to a hypercoagulable state mediated by platelets.…”
Section: Discussionsupporting
confidence: 61%
“…In this context, experimental studies have already shown that platelets are main contributors to microvascular injury and rarefaction of tubulointerstitial capillaries (49). In ANCA-associated renal vasculitis, the occurrence of tubulointerstitial injury independent of glomerular lesions has already been described (50)(51)(52)(53). Our observations might indicate that the tubulointerstitial compartment is particularly susceptible to a hypercoagulable state mediated by platelets.…”
Section: Discussionsupporting
confidence: 61%
“…A detailed mechanism for AAV-associated interstitial nephritis remains unknown [ 19 ], with limited clues from the literature. Peritubular capillaritis is common in AAV with glomerular capillaritis, vasculitis in vessels, and extravascular granuloma formation [ 18 ]. This result indicated that the loss of CD34 vascular endothelial markers occurs in the early phase of the disease [ 19 ] with infiltration of neutrophils and mononuclear cells into tubular epithelial cells, which was associated with tubular basement membrane lysis.…”
Section: Discussionmentioning
confidence: 99%
“…A few AAV patients with acute interstitial nephritis progressed to crescentic glomerulonephritis. Their confounding factors were cimetidine treatment and other unknown mechanisms [ 10 , 18 , 22 ]. Further research is required to reveal the exact pathogenesis of AAV-associated interstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the extensive tubulointerstitial lesions were related to renal dysfunction rather than the glomerular lesions in our case. Most reports of AAV have focused on glomerular lesions due to crescent formation (12), but there have been reports of AAV with tubulointerstitial nephritis as the predominant lesion (14,15). As described in the reported case, it is essential to consider drug-induced tubulointerstitial nephritis in our case as well, although eosinophil infiltration is scant.…”
Section: B: Fibrinoid Necrosis (Arrow) Periodic Acid-schiff (Pas) Sta...mentioning
confidence: 73%